Implementation of the Combination Model of Expectation Confirmation Theory and WebQual 4.0 in CRM Analysis of Post-Pandemic ShopeeFood Customer Loyalty - Agus Bayu Pamungkas; Budi Prasetiyo (Universitas Negeri Semarang, 2025)
Online Food Delivery (OFD) is a service where consumers can order food online through a specific platform or application, and the food is then prepared by restaurants or food service providers and delivered directly to the consumer's address. Shopee is one of the largest and most popular e-commerce platforms in Indonesia, with one of its rapidly growing services being ShopeeFood, a food delivery service feature. Shopee has also expanded into several Southeast Asian countries and Taiwan since its launch in 2015. The aim of this research is to demonstrate the implementation of a combination of WebQual 4.0 and ECT in analyzing the relationship between CRM and customer loyalty and to determine the influence of the relationships among variables studied on ShopeeFood customer loyalty. This research adopts a quantitative approach with sample criteria including people from Java Island who have used ShopeeFood and are between 19-34 years old. This study obtained valid data from 186 respondents through a survey distributed via social media. The majority of respondents were female, aged 19-26, and were high school or vocational school graduates. The results show that of the 9 hypotheses tested, 7 were accepted and 2 were rejected. Among these hypotheses, several factors affecting user loyalty towards various online food delivery platforms include user satisfaction and CRM. Additionally, information quality, expectation, and CRM also influence user satisfaction. Expectation also affects confirmation. On the other hand, the tests conducted on the usability, service quality, and confirmation variables did not influence user satisfaction in this study.